Waking Leviathan - Matthew Skjonsberg (Research in Urbanism Series, 2015)
There still exists in the collective global imagination a ghostly ‘image of progress’ framed by a nature-dominating narrative that distorts reality. As living standards rise worldwide, the demand for natural resources is accelerating in a familiar pattern: cities eat the rural, and the rural eats the wilderness. Ecology, society and economy are not the either/or variables they are often portrayed as being: there is no society without ecology, and no economy without society, each is embedded in context. As globalised societies become increasingly urban, the notion that cities ought to become self-sufficient has been widely popularised in both the architectural profession and in academia, legitimated through the use of the term autopoiesis (Greek αυ’τo ‘self’ and ποίησις ‘creation’), borrowed from the field of chronobiology. The opposite of autopoiesis, a closed process in which context might be an afterthought, is allopoiesis, the process whereby an organisationally open system produces something other than itself. Reality is many-layered and emphatically simultaneous, and while designers are busy fine-tuning daydreams of ‘self-sufficient cities’, regions and ecological systems now supporting real cities are being fragmented and erased in vast swaths, often taking once thriving cities along with them, further accelerating centralised urbanisation. Frank Lloyd Wright’s The Living City is a conceptual rural urban model for decentralised development that attempts, through its evolution in several iterations (from 1901 till 1958) to provide a humane alternative to centralised commercial urbanism. Wright’s life (1867-1959) and work spanned from the Victorian age to the space age, and The Living City is arguably his most ambitious attempt to ‘bridge the gap’. In arguing for contextual, open-ended planning methods it provides a suitable polar counterpoint to contemporary notions of cities as self-sufficient. As a precedent stimulating awareness of the fundamental need for the ‘humane proportion’ of industry and agronomy, it is of urgent relevance today.